HUBUNGAN MINAT MEMBATIK DENGAN PRESTASI BELAJAR BATIK SISWA SEKOLAH MENENGAH KEJURUAN - Tin Dels Marce Ndawu (UNIVERSITAS SARJANAWIYATA TAMANSISWA, 2018)
The purpose of this study to determine (1) batik workinterest (2) batik learning achievement (3) batik interestrelationship with the batik learning achievementsof tenthgrades student in Yogyakarta 5 vocational high school.The study of population was tenth grade who were sixtyonestudents.Instrument in this study was a questionnaireand documentation. This study used a sampling techniquethat was developed by Isaac and Michael. Data analysistechnique used descriptive analysis technique andcorrelational analysis with the analysis that precededrequirement normality test, linearity. Hypothesis testingused product moment correlation analysis.The result ofthis study indicated that interest in batik category quite63,9% and batik learning achievements category quite47,5%. The value of r bigger than r table of r ( 0,445 â‰¥0,244 ). The given amount of donations can be seen fromthe determinant coefficient value by 0,198. It showed theamount of donations by batik interest to batik learningachievement by 19,8%, the restby 80,2% of the donationscame from social intercourse, family environment andneighborhood. Thus batik working interest could affectstudent batik learning achievements.